1997
DOI: 10.1038/ki.1997.41
|View full text |Cite
|
Sign up to set email alerts
|

Depressed expression of calcium receptor in parathyroid gland tissue of patients with hyperparathyroidism

Abstract: The factors involved in abnormal parathyroid cell secretory function and growth in patients with primary (I degree) and secondary (II degree) hyperparathyroidism are still incompletely understood. We compared the expression of the calcium-sensing receptor (CaR) at the gene message and the protein level in parathyroid tissue obtained from patients with I degree non-uremic or II degree uremic hyperparathyroidism with that in normal parathyroid tissue, using in situ hybridization and immunohistochemistry techniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
233
1
13

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 456 publications
(258 citation statements)
references
References 26 publications
11
233
1
13
Order By: Relevance
“…We previously reported that MIBI uptake by parathyroid glands did not reflect the rate of mitochondria-rich cells [29]. Gogusev et al [30] recently reported that the number of calcium sensors on the surface of N-type hyperplastic cells was lower than that found in D-type cells. Tc-MIBI is sequestered inside the cytoplasm and mitochondria, and its degree of cellular incorporation and retention depends on the electric potential generated through the cellular and mitochondrial membrane [31].…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that MIBI uptake by parathyroid glands did not reflect the rate of mitochondria-rich cells [29]. Gogusev et al [30] recently reported that the number of calcium sensors on the surface of N-type hyperplastic cells was lower than that found in D-type cells. Tc-MIBI is sequestered inside the cytoplasm and mitochondria, and its degree of cellular incorporation and retention depends on the electric potential generated through the cellular and mitochondrial membrane [31].…”
Section: Discussionmentioning
confidence: 99%
“…The same was seen in the tubulointerstitium by immunohistochemistry. The changes in glomerular CaSR expression correspond to changes observed by others in the parathyroid glands (9,14).…”
Section: Discussionmentioning
confidence: 99%
“…PG from patients with severe secondary or tertiary hyperparathyroidism (HPT) have an elevated set-point for Ca ϩϩ in vitro (5). A substantial reduction in the expression of the Ca ϩϩ -sensing receptor (CaR) protein and mRNA has been demonstrated in hyperplastic parathyroid glands from uremic patients (6,7). 1,25(OH) 2 D 3 dramatically decreases PTH gene transcription (8), and it has been proposed that this sterol also influences the sensitivity of the parathyroid cells to Ca ϩϩ (9).…”
mentioning
confidence: 99%